Challenges When Expanding Transcatheter Aortic Valve Implantation to Younger Patients - De Backer, Ole; Søndergaard, Lars (Frontiers in Cardiovascular Medicine, 2018)
The rapid expansion of transcatheter aortic valve implantation (TAVI) has been based upon robust clinical evidence derived from randomized controlled trials and large-scale international and national registries. Over the past decade, TAVI has evolved into a safe and effective procedure with predictable and reproducible outcomes. As a consequence, the TAVI technology is increasingly used to treat patients with a lower risk profile and the volume of TAVI now exceeds surgical aortic valve replacement (SAVR) in some countries. It may be anticipated that, in the near future, the majority of patients with severe symptomatic aortic valve stenosis will undergo TAVI as first line therapy, regardless of their age and risk profile. This article identifies some of the specific challenges that lie ahead when considering expansion of TAVI to younger patients.